2021
DOI: 10.3390/microorganisms9091956
|View full text |Cite
|
Sign up to set email alerts
|

A Small Virus to Deliver Small Antibodies: New Targeted Therapies Based on AAV Delivery of Nanobodies

Abstract: Nanobodies are camelid-derived single-domain antibodies that present some advantages versus conventional antibodies, such as a smaller size, and higher tissue penetrability, stability, and hydrophilicity. Although nanobodies can be delivered as proteins, in vivo expression from adeno-associated viral (AAV) vectors represents an attractive strategy. This is due to the fact that AAV vectors, that can provide long-term expression of recombinant genes, have shown an excellent safety profile, and can accommodate ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…Such a subunit is structurally homologous to the variable domains of the heavy chain-only antibodies (V HH ) found in camelids termed nanobodies. These small (of nanometric size) molecules were proven to have good stability, solubility, and tissue permeability which makes them superior reagents in various applications including cell biology, diagnostics, and therapeutic use [ 54 , 55 , 56 , 57 , 58 ]. We believe that the similar use of isolated variable subunits from common antibodies (V H or V L ), retaining high affinity to the antigen, in particular, in biochemical competition assays and imaging may result in higher mapping precision for ligand binding sites and image quality with faster sample processing.…”
Section: Discussionmentioning
confidence: 99%
“…Such a subunit is structurally homologous to the variable domains of the heavy chain-only antibodies (V HH ) found in camelids termed nanobodies. These small (of nanometric size) molecules were proven to have good stability, solubility, and tissue permeability which makes them superior reagents in various applications including cell biology, diagnostics, and therapeutic use [ 54 , 55 , 56 , 57 , 58 ]. We believe that the similar use of isolated variable subunits from common antibodies (V H or V L ), retaining high affinity to the antigen, in particular, in biochemical competition assays and imaging may result in higher mapping precision for ligand binding sites and image quality with faster sample processing.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of α-syn fibril-specific antibodies in reducing α-syn pathology has been reported 27 . However, antibodies have poor membrane penetration ability and are usually not functional in the reducing cytosolic environment 21,22 , and therefore, can only extracellular α-syn fibrils [23][24][25][26][27]67 , limiting their impact on the pre-existing intracellular α-syn aggregates. A study has reported that single-chain antibody fragment (scFv) D5 binding to α-syn oligomer can inhibit α-syn fibrillization 68 and toxicity 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, α-syn pathology and propagation are observed mainly inside neurons and α-syn is more abundant in neurons than in glia cells, indicating that the intracellular α-syn significantly drives the pathogenesis [17][18][19] . There have been tremendous efforts on the development of antibodies against α-syn (reviewed in Vaikath et al 20 ); however, due to the large size and structural complexity, antibodies have limited penetrability through the plasma membrane 21,22 . Consequently, α-syn antibodies typically do not enter cells but only target the extracellular α-syn fibrils [23][24][25][26][27] , not accessible to the essential target, the intracellular pathologic α-syn species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of the simplicity of genetic manipulation of single-domain antibodies, we fused them to the Fc domain of mouse IgG, generating larger, homodimeric molecules with improved PD-1/PD-L1 inhibition capacity. This strategy has already been used to optimize nanobodies in several preclinical studies and in some candidates that have reached clinical trials [ 138 ]. SFV vectors encoding these nanobody-Fc fusion proteins showed potent antitumor activity in mouse models of CRC and melanoma, outperforming control vectors encoding conventional antibodies against PD-1 and PD-L1 [ 136 ].…”
Section: Viral Vectors To Deliver Immunomodulatory Antibodiesmentioning
confidence: 99%